Clinical and laboratory approach to a neonate suspected of an inborn error of metabolism - Kang, Ellen S. (The Turkish Journal of Pediatrics, 1999)
Metabolic and molecular advances have led to the identification of hundreds of inborn errors of metabolism, too many for most to recall from memory alone without referral to authoritative compilations of published works, often assembled in formidable (in size and scope) books weighing many pounds. Those encountering such disorders in neonates face unique and special challenges because of the fragility of their patients, the rapidity with which these conditions progress, and the fact that many of the expressions of inherited metabolic disturbances mimic other serious conditions, thereby delaying diagnosis and placing the newborn at serious risk for survival.A simple algorithm to quickly establish the diagnosis of the numerous inborn errors of metabolism that have been reported would be helpful. However, because of the diversity of the conditions and defects that can occur, numerous subsets would have to be developed to cover the full spectrum of conditions that may be encountered.In this report, conditions to consider when confronted with a newborn suspected of an inborn error of metabolism are grouped, based primarily on the presenting clinical findings in the neonate together with laboratory tests that can be performed by most clinical laboratories. Further workup to narrow the possibility should follow, confirming the diagnosis by special tests with consultation from specialists who are more familiar with these conditions. Establishing the diagnosis by specific enzymatic assay would require the involvement of specialists with the laboratory resources to perform the tests. The approach suggested is by no means exhaustive. It does not include genetic conditions that are unlikely to be expressed in the newborn period, nor those that are extremely rare in occurrence.Only an abbreviated historical account is presented, omitting many important citations to individual papers from a large family of dedicated investigators. Many citations are to chapters in the three volumes of The Metabolic and Molecular Bases of Inherited Disease by Scriver, Beaudet, Sly and Valle, with the expectation that the reader would pursue other details cited in these works and those published since then, as may be clinically indicated, in their workup of any neonate suspected of an inborn error of metabolism.